On interaction between humanitarian knowledge and architectural theory and practice - Kholodova Lyudmila P.; Tsorik Alena V. (Архитектон)
The article is devoted to the reassessment of the role of fundamental architectural science within the context of the modern architectural process. The article offers a consistent analysis of the correlation between the tools of architectural science and the nomenclature of scientific specialities, spheres of influence of applied and fundamental sciences, emergence and demand for new areas of knowledge about urban life, and education of would-be architects. Examples are provided to show how human and social sciences are integrated into architectural science and practice.